Metal part suitable for water electrolysis hydrogen production and preparation method

Through electrochemical pickling and subsequent electrical deposition or physical gas deposition technology, the distribution and load of precious metal particles on electrolyte hydrogen metal components can be controlled, which solves the problem of high precious metal load and insufficient durability. Performance improvement.

CN119332280AActive Publication Date: 2025-01-21北京怀柔实验室 +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411525059.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-21
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

In the prior art, the loading of precious metal particles on metal parts that produce hydrogen by electrolyzing water is high, resulting in increased cost and insufficient durability, making it difficult to maintain stability in a high potential and acidic medium environment.

Method used

The size and distribution of the precious metal particles are initially controlled through the electrochemical pickling step, and then electrodeposition or physical vapor deposition is used to further control the size and distribution of the precious metal particles to ensure that the precious metal particles are evenly distributed on the surface of the sample, and the particle size is between 10nm and 10nm. Between 180nm and 180nm, the loading capacity is less than 0.3mg/cm2 on both sides.

Benefits of technology

Effectively reduce the load of precious metals, reduce processing costs, and improve the conductivity, erosion resistance and durability of metal components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332280A_ABST
    Figure CN119332280A_ABST
Patent Text Reader

Abstract

The invention discloses a metal part suitable for water electrolysis hydrogen production and a preparation method, and belongs to the technical field of metal material combination. Comprising the following steps: preliminarily controlling the size of noble metal particles and the distribution condition of the noble metal particles on the surface of a sample in the subsequent deposition process by adjusting condition parameters in the pickling process; the condition parameters comprise the pickling temperature range of 25-90 DEG C and the pickling time of 5 minutes to 2 hours; and finally controlling the size of the noble metal particles and the distribution condition of the noble metal particles on the surface of the sample by adopting an electro-deposition or physical vapor deposition mode, so that the noble metal particles are uniformly distributed on the surface of the sample, and the particle size of the noble metal particles is between 10nm and 180nm. According to the preparation method, low precious metal loading capacity can be deposited, the particle size of precious metal particles can be controlled to range from 10 nm to 180 nm, the precious metal loading capacity of the prepared metal part sample is 0.3 mg / cm < 2 > or below on the double faces, the average single-face coating thickness is 70 nm or below, and the processing cost is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal material bonding, and specifically to a metal component suitable for producing hydrogen by electrolysis of water and a preparation method thereof. Background Art

[0002] Industrial pure titanium TA1 is the core material of bipolar plates and porous transport layers in PEM (proton exchange membrane) water electrolysis hydrogen production technology. It is highly favored for its good thermal and electrical conductivity, excellent durability and chemical stability. However, in the actual operating environment of PEM water electrolysis hydrogen production, components made of titanium materials need to face severe corrosion challenges such as high potential, oxygen-rich, high temperature and acidic media. These conditions can easily induce oxidation reactions, which not only increase contact resistance, but also greatly affect the durability of bipolar plates and reduce hydrogen production efficiency. Therefore, it is urgent to construct a coating system with high conductivity, strong corrosion resistance and long durability on the surface of titanium-based bipolar plates and porous transport layers.

[0003] Currently, a variety of coating systems have been developed to meet this demand, mainly including:

[0004] Precious metal coatings: such as platinum, iridium, gold, etc., although they have excellent performance, the high precious metal content pushes up the cost, which seriously restricts the commercialization process of water electrolysis technology.

[0005] Metal-nonmetal doped coating: Metals (such as TiN, ZrC, TiCN, TiNO) are modified by introducing one or more elements such as N, C, O, etc. However, during long-term use, oxygen atoms can easily penetrate into the coating, aggravating oxidation, resulting in increased contact resistance, and durability cannot be guaranteed.

[0006] Non-precious metal doped coating: directly constructing a composite metal coating on the substrate, although the cost is low, it is easy to form a passivation film under the actual working conditions of electrolytic hydrogen production. Although it improves corrosion resistance, the formation of the passivation film also increases the contact resistance, resulting in increased energy consumption and decreased hydrogen production efficiency.

[0007] Hybrid carbon coating: Hybrid carbon coating directly coated on titanium material shows certain potential in the field of fuel cells, but in the high-potential PEM water electrolysis hydrogen production environment, the hybrid carbon coating undergoes irreversible oxidation at high potential, which restricts its long-term stability.

[0008] Although existing coating systems have their own characteristics, they still need to overcome key problems such as high cost, insufficient durability or easy oxidation failure in order to promote the further development and application of PEM water electrolysis hydrogen production technology.

[0009] At present, there are also some related technical studies to solve the above problems. For example, the patent document with publication number CN117947370A discloses a highly conductive, corrosion-resistant porous titanium diffusion layer and its preparation method and application, which records: in step S02, the etched porous titanium diffusion layer is subjected to precious metal particle deposition, and the size of the precious metal deposition particles is controlled to obtain a porous titanium diffusion layer with precious metal deposition. In step S03, the porous titanium diffusion layer deposited with precious metals is subjected to in-situ oxidation layer growth treatment to achieve the fixation of precious metal particles, and obtain a porous titanium diffusion layer with oxide-fixed precious metal particles. Furthermore, in step S03, the growth thickness after the film can be further regulated according to the load. The porous titanium diffusion layer obtained by this method can reduce the contact resistance of the porous titanium diffusion layer, improve its conductivity by converting the conductive material into titanium oxide, and increase the corrosion resistance of the porous titanium; at the same time, the precious metal load in the porous titanium coating is reduced, and the coating bonding strength is increased by in-situ growth of the encapsulation structure. However, the particle size of the precious metal particles obtained by this method is 260-350nm, and the load is 0.3-1.4mg / cm 2 , the effect of reducing the precious metal loading is not very good.

[0010] Obviously, it is very important to reduce the precious metal loading on the surface of metal parts. However, there is no reliable solution in the prior art that can effectively reduce the precious metal loading. Therefore, it is urgent to develop a new metal part suitable for electrolysis of water to produce hydrogen and a preparation method to effectively reduce the precious metal loading on the surface of metal parts. Summary of the invention

[0011] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application provides a metal component suitable for electrolysis of water to produce hydrogen and a preparation method thereof, wherein the size of the precious metal particles and the distribution on the sample surface are preliminarily controlled by an electrochemical pickling step, and then the size of the precious metal particles and the distribution on the sample surface are finally controlled by electrodeposition or physical vapor deposition, thereby effectively reducing the precious metal loading and processing costs.

[0012] To achieve the above objectives, in a first aspect, the present application provides a metal component suitable for electrolyzing water to produce hydrogen, wherein the metal component has a precious metal coating, and the precious metal loading of the precious metal coating is 0.3 mg / cm on both sides. 2 The average single-sided coating thickness is below 70 nm; the precious metal particles on the precious metal coating are uniformly distributed and the particle size of the precious metal particles is between 10 nm and 180 nm, wherein the difference between the maximum particle size and the minimum particle size of the precious metal particles is less than 130 nm, and the average spacing between the precious metal particles is 38 to 227 nm, and the average spacing is defined as the average value of the distances to the N precious metal particles closest to all the precious metal particles, 10 ≥ N ≥ 2.

[0013] Preferably, the metal component is a titanium bipolar plate or a porous transport layer.

[0014] In a second aspect, the present application provides a method for preparing a metal component suitable for producing hydrogen by electrolysis of water, comprising the following steps:

[0015] The size of the precious metal particles and the distribution on the sample surface during the subsequent deposition process are preliminarily controlled by adjusting the condition parameters of the pickling process; the condition parameters include a pickling temperature range of 25 to 90° C. and a pickling time of 5 min to 2 h;

[0016] The size of the precious metal particles and their distribution on the sample surface are ultimately controlled by electrodeposition or physical vapor deposition, thereby ultimately producing a metal component with a precious metal coating;

[0017] Among them, the control parameters of electrodeposition need to meet the current density of 1mA ~ 200mA / cm 2 , the duty cycle is 0% to 60%, and the deposition time is 5s to 600s; the control parameters of physical vapor deposition must meet the etching power of 50 to 300W, the etching time of 5 to 60min, the sputtering power of 50 to 500W, the heating temperature of 100 to 1000°C, and the deposition time of 30 to 3600s.

[0018] Preferably, the step of preliminarily controlling the size of the precious metal particles and their distribution on the sample surface during the subsequent deposition process by adjusting the condition parameters of the pickling process includes: applying a negative potential to the sample by electrochemical pickling to cause hydrogen evolution and hydrogen permeation on its surface, wherein surface hydrogen evolution can make the surface energy of the exposed portion of the sample tend to be consistent, and the probability of depositing precious metal particles tend to be consistent; surface hydrogen permeation can reduce the precious metal ions on the surface of the sample during the deposition process due to the release of hydrogen in the sample, thereby achieving the deposition of precious metal particles with small particle size.

[0019] Preferably, the condition parameters also include the pickling solution being selected from one or a combination of oxalic acid, hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid.

[0020] Preferably, before the step of preliminarily controlling the size of the precious metal particles and their distribution on the sample surface in the subsequent deposition process by adjusting the condition parameters of the pickling process, the step includes: presetting the pre-deposition position of the precious metal particles on the sample surface by physical means.

[0021] Preferably, the step of presetting the pre-deposition position of the precious metal particles on the sample surface by physical means comprises: preparing sub-microholes corresponding to the pre-deposition position on an acid-base resistant and high temperature resistant tape above 100°C or a high temperature resistant mask plate, and sticking it on the sample surface.

[0022] Preferably, the step of preparing sub-microholes corresponding to the pre-deposition position on an acid- and alkali-resistant tape or a high-temperature-resistant mask plate includes: using ultrafast laser drilling technology to drill holes with a diameter between 100nm and 10μm on an acid- and alkali-resistant tape or a high-temperature-resistant mask plate made of PET, PTFE, PVC or PI material, to form a design pattern corresponding to the pre-deposition position.

[0023] Preferably, the step of presetting the pre-deposition position of the noble metal particles on the sample surface by physical means comprises: constructing micrometer-sized arc-shaped metal particles corresponding to the pre-deposition position on the sample surface.

[0024] Preferably, the step of constructing micron-sized arc-shaped metal particles on the sample surface corresponding to the pre-deposition position includes: constructing micron-sized metal particles with a particle size of 0.5 μm to 25 μm on the sample surface by flame spraying, arc spraying, plasma spraying or thermal spraying to form a design pattern corresponding to the pre-deposition position.

[0025] Preferably, the micron-sized arc-shaped metal particles can withstand harsh working conditions of water electrolysis to produce hydrogen and maintain corrosion resistance, and the metal component is selected from one or more corrosion-resistant elements of Ti, Zr, Nb, Ta, Mo and W.

[0026] Preferably, the step of ultimately controlling the size and distribution of the precious metal particles on the sample surface by electrodeposition or physical vapor deposition includes: using electrodeposition to control the size and distribution of the precious metal particles by adjusting the parameters of the pulse power supply, current, frequency, duty cycle and deposition time; or, using physical vapor deposition to control the size and distribution of the precious metal particles by adjusting the power, target spacing and deposition time.

[0027] Based on the above technical solution, it can be seen that the metal component and preparation method suitable for hydrogen production by electrolysis of water in the present application have the following beneficial effects compared with the prior art:

[0028] The present invention is applicable to the preparation method of metal parts for electrolyzing water to produce hydrogen. The size of the precious metal particles and the distribution on the sample surface are preliminarily controlled by an electrochemical pickling step, and then the size of the precious metal particles and the distribution on the sample surface are finally controlled by electrodeposition or physical vapor deposition, so that the precious metal particles are evenly distributed on the sample surface and the size of the precious metal particles is between 10nm and 180nm. The precious metal loading of the prepared metal part sample is 0.3mg / cm on both sides. 2The average single-sided coating thickness is below 70 nm, and the average spacing between the precious metal particles is 38 to 227 nm, which effectively reduces the precious metal loading and reduces the processing cost.

[0029] Other features and advantages of the present application will be described in the subsequent description, and in part will become apparent from the description, or it may be understood through the implementation of the present application that the objects and other advantages of the present application can be realized and obtained through the structures particularly pointed out in the written description, claims, and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a flow chart of a first embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolysis of water in the present application;

[0031] Figure 2 This is a SEM microscopic morphology of a titanium substrate sample with a low platinum loading coating obtained by a method for preparing a metal component suitable for electrolyzing water to produce hydrogen in this application;

[0032] Figure 3 This is a flow chart of a second embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolyzing water in the present application;

[0033] Figure 4 This is a flow chart of a third embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolyzing water in the present application;

[0034] Figure 5 This is a flow chart of a fourth embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolyzing water in the present application;

[0035] Figure 6 This is a flow chart of a fifth embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolyzing water in the present application. DETAILED DESCRIPTION

[0036] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0037] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0038] In view of the deficiencies in the prior art, an object of the present invention is to provide a method for preparing a metal component suitable for producing hydrogen by electrolysis of water, in the hope of effectively reducing the precious metal loading on the surface of the metal component.

[0039] The basic idea of ​​the present invention is to preliminarily control the size of the precious metal particles and the distribution of the precious metal particles on the sample surface by using an electrochemical pickling step, and then finally control the size of the precious metal particles and the distribution of the precious metal particles on the sample surface by electrodeposition or physical vapor deposition, so that the precious metal loading of the precious metal coating is 0.3 mg / cm on both sides. 2 Below, the average single-sided coating thickness is below 70nm, the precious metal particles are evenly distributed on the sample surface and the size of the precious metal particles is between 10nm and 180nm, wherein the difference between the maximum and minimum particle sizes of the precious metal particles is less than 130nm, and the average spacing between the precious metal particles is 38 to 227nm, wherein the average spacing is defined as the average value of the distances to the N nearest precious metal particles to all the precious metal particles, 10≥N≥2.

[0040] The method specifically comprises:

[0041] The size of the precious metal particles and their distribution on the sample surface during the subsequent deposition process are preliminarily controlled by adjusting the condition parameters of the electrochemical pickling process; the condition parameters include a pickling temperature range of 25 to 90°C and a pickling time of 5 min to 2 h; further preferably, the pickling temperature range can also be selected from 40 to 60°C, and the pickling time can be selected from 20 min to 2 h.

[0042] The size of the precious metal particles and their distribution on the sample surface are finally controlled by electrodeposition or physical vapor deposition, so that the precious metal particles are evenly distributed on the sample surface and the particle size of the precious metal particles is between 10nm and 180nm, thereby finally obtaining a metal part with a precious metal coating; wherein the control parameters of the electrodeposition need to meet the current density of 1mA to 200mA / cm 2 , the duty cycle is 0% to 60%, and the deposition time is 5s to 600s; the control parameters of physical vapor deposition must meet the etching power of 50 to 300W, the etching time of 5 to 60min, the sputtering power of 50 to 500W, the heating temperature of 100 to 1000°C, and the deposition time of 30 to 3600s.

[0043] The surface energy difference of the metal component sample surface after pickling using a specific electrochemical method is very small, so it can be ensured that the deposition effect is a spaced uniform distribution. And by controlling the condition parameters of the electrochemical pickling process, hydrogen can be evolved and permeated on the sample surface. Surface hydrogen evolution can make the surface energy of the exposed part of the sample tend to be consistent, and the probability of depositing precious metal particles tends to be consistent; surface hydrogen permeation can make the sample reduce the precious metal ions on its surface due to the release of hydrogen in the sample during the deposition process, thereby achieving the deposition of small-sized precious metal particles. By adjusting the condition parameters of the electrochemical pickling process to the above parameter range, the effect of the deposition of precious metal particles on the sample surface can be achieved with a spaced uniform distribution. In this way, the size of the precious metal particles and their uniform distribution on the sample surface are finally controlled, and the precious metal loading of the prepared metal component sample is 0.3mg / cm on both sides. 2 The average single-sided coating thickness is below 70nm, which effectively reduces the precious metal loading and reduces processing costs.

[0044] Embodiment 1

[0045] This embodiment provides a metal component suitable for electrolyzing water to produce hydrogen. The metal component has a precious metal coating. The precious metal loading of the precious metal coating is 0.3 mg / cm on both sides. 2 The average single-sided coating thickness is below 70nm; the precious metal particles on the precious metal coating are evenly distributed and the size of the precious metal particles is between 10nm and 180nm, wherein the difference between the maximum and minimum particle sizes of the precious metal particles is less than 130nm, and the average spacing of the precious metal particles is 38 to 227nm, and the average spacing is defined as the average distance of the N precious metal particles closest to all the precious metal particles, 10≥N≥2. Specifically, the metal component can be a titanium bipolar plate or a porous transport layer.

[0046] Preferably, when the size of the precious metal particles is between 10nm and 80nm, the difference between the maximum and minimum particle sizes of the precious metal particles is less than 15nm, and the average spacing between the precious metal particles is 38-60nm. At this time, since the size difference between the precious metal particles is smaller, the size of the precious metal particles is more uniform, and the overall distribution distance is also more uniform, so the precious metal loading of the precious metal coating can also be 0.3mg / cm on both sides. 2 Below is the technical effect of an average single-sided coating thickness of less than 70nm.

[0047] Embodiment 2

[0048] In order to develop a method that can effectively reduce the precious metal loading on the surface of metal component samples, the inventors conducted in-depth research on the electrochemical pickling process and deposition process control, and proposed a method for preparing metal components suitable for hydrogen production by electrolysis of water.

[0049] Specifically, Figure 1 As shown, a method for preparing a metal component suitable for electrolyzing water to produce hydrogen comprises the following steps:

[0050] S1. Select titanium felt of fixed size as sample, pickle the sample with oxalic acid of concentration of 5% to 20%, the pickling temperature is 25 to 90°C, and the pickling time is 5min to 2h;

[0051] S2. After pickling, rinse the sample repeatedly with deionized water, wipe it dry and set aside;

[0052] S3, placing the pickled sample and the fixed-size platinum sheet in an electroplating solution with a temperature range of 25 to 70°C for electroplating, and controlling the size and distribution of the precious metal particles by adjusting the parameters of the pulse power supply, the current, the frequency, the duty cycle and the deposition time. The metal component may be a titanium bipolar plate or a porous transport layer.

[0053] Preferably, the control parameters of the electrodeposition need to satisfy the current density of 5 mA to 200 mA / cm 2 , the duty cycle is 15% to 60%, and the deposition time is 60s to 600s.

[0054] Specifically, in this embodiment, step S1 selects 5cm×5cm titanium felt as a sample, and uses oxalic acid with a concentration of 10% to perform static pickling on the sample, the pickling temperature is 80°C, and the pickling time is 1h; the oxide film on the surface of the bipolar plate and the porous transport layer is removed by adjusting the above pickling condition parameters (the porous transport layer is a porous structure, and the parameters and methods are adjusted to make the surface exposed area fully pickled, so as to facilitate the attachment of precious metal particles in the exposed area. In step S3, the pickled sample and the 5cm×5cm platinum sheet are placed in the electroplating solution heated to 35°C in advance, and the sample is connected to the negative electrode of the pulse power supply, and the positive electrode is connected to the platinum sheet. Among them, the parameters, current, frequency, duty cycle and deposition time of the pulse power supply are adjusted to control the size and distribution of the precious metal particles. In this embodiment, the pulse power supply parameters are specifically set to: the current is 5mA, the duty cycle is 15%, the frequency is 50Hz, and the deposition time is 200s. The obtained titanium substrate sample low platinum loading coating SEM microscopic morphology is as follows Figure 2 As shown in (a), the precious metal loading of the precious metal coating formed by the method of this embodiment is 0.3 mg / cm on both sides. 2Below, the average single-sided coating thickness is below 50nm, the size of the formed precious metal particles is between 50nm and 180nm, wherein the difference between the maximum and minimum particle sizes of the precious metal particles is less than 130nm, and the average spacing of the precious metal particles is 38 to 227nm, and the average spacing is defined as the average value of the distances of the 8 precious metal particles closest to all the precious metal particles. It should be noted that in addition to the static pickling method used in this embodiment, the pickling method can also be achieved by ultrasonic pickling, stirring pickling, electrochemical pickling, etc.

[0055] Further, preferably, while ensuring that the other parameters remain the same as those in Example 1, the SEM microscopic morphology of the low platinum loading coating of the titanium substrate sample obtained by changing the static pickling method to the electrochemical pickling method is as follows: Figure 2 As shown in (b), it can be seen that the precious metal loading of the precious metal coating formed in this way is also 0.3 mg / cm on both sides. 2 Below, the average single-sided coating thickness is also below 70nm, but the size of the precious metal particles is between 10nm and 80nm, the difference between the maximum and minimum particle sizes of the precious metal particles is less than 15nm, the particle size is more uniform, and the effect is better than that of the static pickling method. This is because a negative potential is applied to the sample by electrochemical pickling to cause hydrogen evolution and hydrogen permeation on its surface. The surface hydrogen evolution can make the surface energy of the exposed part of the sample tend to be consistent, and the probability of depositing precious metal particles tends to be consistent, so that the difference in the size of the precious metal particles is very small. And under the conditions of electrochemical pickling, the average spacing between the precious metal particles is 38 to 60nm, and the average spacing is defined as the average distance of the 8 precious metal particles closest to all the precious metal particles.

[0056] Further, preferably, when the electroplating current in Example 1 is 0A (i.e., no power is applied), the deposition time is 2h, and the static pickling method is changed to the electrochemical pickling method, the SEM microscopic morphology of the titanium substrate sample with low platinum loading coating is as follows: Figure 2 As shown in (c), it can be seen that the precious metal loading of the precious metal coating formed in this way is also 0.3 mg / cm on both sides. 2 The average single-side coating thickness is also below 70 nm, and the effect is better than that of the static pickling method.

[0057] Titanium felt is a porous titanium material with high porosity and good conductivity. Titanium felt can be used as a porous transport layer or as part of a bipolar plate to improve the efficiency and durability of water electrolysis hydrogen production equipment. When depositing precious metal particles on the surface of titanium felt, we expect the precious metal particles to be uniformly deposited on the surface of titanium felt. Therefore, in this embodiment, a negative potential is applied to the sample by electrochemical pickling to cause hydrogen evolution and hydrogen permeation on its surface. Surface hydrogen evolution can make the surface energy of the exposed part of the sample tend to be consistent, and the probability of depositing precious metal particles tends to be consistent; surface hydrogen permeation can make the sample reduce the precious metal ions on its surface due to the release of hydrogen in the sample during the deposition process, thereby achieving the deposition of small-size precious metal particles. By adjusting the condition parameters of the electrochemical pickling process to perform according to the above parameter range, the effect of the deposition of precious metal particles on the surface of the sample can be achieved as a spaced uniform distribution.

[0058] The present invention relates to a method for preparing a titanium bipolar plate and a porous transport layer for producing hydrogen by electrolysis of water, which effectively reduces the loading of precious metals (the loading on the market is more than 0.8 mg / cm 2 ). No, the titanium bipolar plate for producing hydrogen by electrolysis of water and the porous transport layer coating of the present invention have high electrical conductivity, corrosion resistance and durability while having a low noble metal loading.

[0059] Embodiment 3

[0060] like Figure 3 FIG. 1 is a flow chart of a second embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolysis of water according to the present application. In this embodiment, the preparation method includes:

[0061] S1. Use ultrafast laser drilling technology to drill holes with a diameter of 100nm to 10μm on a PET tape that is resistant to acid and alkali and high temperatures above 100°C, and stick both sides of the PET tape to the surface of the titanium felt sample;

[0062] S2. Use oxalic acid with a concentration of 5% to 20% to pickle the sample at a temperature of 25 to 90°C for 5 minutes to 2 hours;

[0063] S3. After pickling, rinse the sample repeatedly with deionized water, wipe it dry and set aside;

[0064] S4, placing the pickled sample and the fixed-size platinum sheet into an electroplating solution in a temperature range of 25 to 70° C. for electroplating, and controlling the size and distribution of the precious metal particles by adjusting the parameters of the pulse power supply, the current, the frequency, the duty cycle and the deposition time;

[0065] S5. Tear off the tape stuck on the surface of the titanium felt sample.

[0066] Preferably, the control parameters of the electrodeposition need to satisfy the current density of 25 mA to 200 mA / cm 2 , the duty cycle is 25% to 60%, and the deposition time is 30s to 600s.

[0067] Specifically, in this embodiment, in step S1, ultrafast laser drilling technology is used to punch 1 μm holes on an acid- and alkali-resistant PET tape that is resistant to high temperatures above 100°C, wherein the distribution of the holes can be designed by oneself; in step S2, 10% sulfuric acid is used for pickling, and heat treatment is performed during pickling, the heating temperature is 60°C, and the pickling time is 1.2h; the pickling method can be static pickling, ultrasonic pickling, stirring pickling, electrochemical pickling, etc., and the oxide film on the surface of the bipolar plate and the porous transport layer is removed by adjusting the above pickling condition parameters (the porous transport layer is a porous structure, and the parameters and methods are adjusted to make the surface exposed area pickled sufficiently, so as to facilitate the attachment of precious metal particles in the exposed area). In step S3, the pickled titanium substrate sample is washed with deionized water for more than 3 times. In step S4, the pickled sample and a 5cm×5cm platinum sheet are placed in an electroplating solution heated to 40°C in advance, and the sample is connected to the negative electrode of the pulse power supply, and the positive electrode is connected to the platinum sheet. The parameters of the pulse power supply, current, frequency, duty cycle and deposition time are adjusted to control the size and distribution of the precious metal particles. In this embodiment, the pulse power supply parameters are specifically set to: current of 100 mA, duty cycle of 25%, frequency of 50 Hz, deposition time of 140 s, and the precious metal loading of the formed precious metal coating is 0.3 mg / cm on both sides. 2 Below, the average single-side coating thickness is below 40nm, and the size of the formed precious metal particles is between 50nm and 180nm.

[0068] In this embodiment, a negative potential is applied to the sample by electrochemical pickling to cause hydrogen to be deposited on its surface. By adjusting the condition parameters of the electrochemical pickling process to be performed within the above parameter range, the surface energy difference of the metal component sample surface after pickling is very small, so the effect of deposition on the sample surface is a uniform distribution with intervals. Specifically, in this embodiment, a negative potential is applied to the sample by electrochemical pickling to cause hydrogen to be deposited and permeated on its surface. The surface hydrogen deposition can make the surface energy of the exposed part of the sample tend to be consistent, and the probability of depositing precious metal particles tends to be consistent; the surface hydrogen permeation can reduce the precious metal ions on its surface due to the release of hydrogen in the sample during the deposition process, thereby achieving the deposition of small-sized precious metal particles.

[0069] The titanium bipolar plate and porous transport layer coating scheme for producing hydrogen by electrolysis of water effectively reduces the precious metal loading, and can simultaneously have high conductivity, corrosion resistance and durability, thus ensuring its long service life under working conditions.

[0070] Embodiment 4

[0071] like Figure 4 As shown, it is a flow chart of a third embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolysis of water in the present application. In this embodiment, the preparation method includes:

[0072] S1. Use ultrafast laser drilling technology to drill holes with a diameter of 100nm to 10μm on a PET tape that is resistant to acid and alkali and high temperatures above 100°C, and stick both sides of the PET tape to the surface of the titanium felt sample;

[0073] S2. Use oxalic acid with a concentration of 5% to 20% to pickle the sample at a temperature of 25 to 90°C for 5 minutes to 2 hours;

[0074] S3. After pickling, rinse the sample repeatedly with deionized water, wipe it dry and set aside;

[0075] S4, performing physical vapor deposition on the pickled sample, and controlling the size and distribution of the noble metal particles by adjusting power, target spacing and deposition time;

[0076] S5. Tear off the tape stuck on the surface of the titanium felt sample.

[0077] Preferably, the control parameters of physical vapor deposition need to meet the following requirements: etching power of 100-300 W, etching time of 10-60 min, sputtering power of 100-500 W, heating temperature of 200-1000° C., and deposition time of 1000-3600 s.

[0078] Specifically, in this embodiment, in step S1, ultrafast laser drilling technology is used to punch 150nm holes on the acid- and alkali-resistant, high-temperature-resistant PET tape above 100°C, wherein the distribution of the holes can be designed by oneself; in step S2, nitric acid with a concentration of 10% is used for pickling, and heat treatment is performed during pickling, the heating temperature is 90°C, and the pickling time is 50min; the pickling method can be static pickling, ultrasonic pickling, stirring pickling, electrochemical pickling, etc., and the oxide film on the surface of the bipolar plate and the porous transport layer is removed by adjusting the above pickling condition parameters (the porous transport layer is a porous structure, and the parameters and methods are adjusted to make the exposed area of ​​its surface fully pickled, so as to facilitate the attachment of precious metal particles in the exposed area). In step S3, the titanium substrate sample after pickling is washed with deionized water for more than 3 times. In step S4, physical vapor deposition is performed on the pickled sample, and the size and distribution of the precious metal particles are controlled by adjusting the power, target spacing and deposition time. Specifically, the platinum target and the sample are connected to the negative pole of a DC power supply or grounded, and the DC power supply provides the electric field required for sputtering. Further, in this embodiment, the power of the magnetron sputtering DC sputtering is 500W, the target spacing is 8cm, the sputtering time is 30min, and the precious metal loading of the formed precious metal coating is 0.3mg / cm on both sides. 2Below, the average single-side coating thickness is below 30nm, and the size of the formed precious metal particles is between 10nm and 40nm.

[0079] Embodiment 5

[0080] like Figure 5 As shown, it is a flow chart of a fourth embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolysis of water in the present application. In this embodiment, the preparation method includes:

[0081] S1. Constructing micron-sized metal particles with a particle size of 0.5 μm to 25 μm on the surface of the sample by thermal spraying;

[0082] S2. Use oxalic acid with a concentration of 5% to 20% to pickle the sample at a temperature of 40 to 60°C for 20 minutes to 2 hours;

[0083] S3. After pickling, rinse the sample repeatedly with deionized water, wipe it dry and set aside;

[0084] S4. Place the pickled sample and a fixed-size platinum sheet in an electroplating solution with a temperature range of 25 to 70°C for electroplating, and control the size and distribution of the precious metal particles by adjusting the parameters of the pulse power supply, current, frequency, duty cycle and deposition time.

[0085] Specifically, in this embodiment, in step S1, micron-sized arc-shaped metal particles with a particle size of 0.8 μm are constructed on the sample surface by thermal spraying. It should be noted that constructing micron-sized arc-shaped metal particles corresponding to the pre-deposition position on the sample surface is only a preferred method of this application. Specifically, micron-sized metal particles of other shapes corresponding to the pre-deposition position can also be selected on the sample surface, as long as a bulge can be formed relative to the sample surface. In step S2, hydrochloric acid with a concentration of 15% is used for pickling, and heat treatment is performed during pickling. The heating temperature is 50°C and the pickling time is 50 minutes. The pickling method can be static pickling, ultrasonic pickling, stirring pickling, electrochemical pickling, etc., and the oxide film on the surface of the bipolar plate and the porous transport layer is removed by adjusting the above pickling condition parameters (the porous transport layer is a porous structure, and the parameters and methods are adjusted to make the surface exposed area fully pickled, so as to facilitate the attachment of precious metal particles in the exposed area). In step S3, the titanium substrate sample after pickling is washed with deionized water for more than 3 times. In step S4, the pickled sample and a 5cm×5cm platinum sheet are placed in a plating solution preheated to 45°C, and the sample is connected to the negative electrode of the pulse power supply, and the positive electrode is connected to the platinum sheet. The size and distribution of the precious metal particles are controlled by adjusting the parameters of the pulse power supply, the current, the frequency, the duty cycle and the deposition time. In this embodiment, the pulse power supply parameters are specifically set to: the current is 1.4A, the duty cycle is 25%, the frequency is 50Hz, the deposition time is 160s, and the precious metal loading of the formed precious metal coating is 0.3mg / cm on both sides. 2 Below, the average single-side coating thickness is below 60nm, and the size of the formed precious metal particles is between 50nm and 180nm.

[0086] Since non-precious metal doped coatings are easily passivated under working conditions, they have good corrosion resistance, but the contact resistance increases due to the formation of the passivation film, and the durability is poor. In this embodiment, a layer of precious metal is deposited on micron-sized metal particles composed of several corrosion-resistant elements such as Ti, Zr, Nb, Ta, Mo and W, and the precious metal loading is ensured to be 0.3 mg / cm on both sides. 2The following is a further explanation of why the precious metal particles are preferentially deposited at the positions corresponding to the micron-sized metal particles: The micron-sized metal particles form protrusions relative to the sample surface. On the one hand, during the pickling corrosion process, the protruding part of the metal material often becomes the anode (i.e., the electron donor), while the concave or the surrounding flatter part may serve as the cathode (i.e., the electron acceptor). In an acidic environment, the anode will accelerate the dissolution (this is because the contact area between the protruding part and the electrolyte is relatively large, and the current density is high, which accelerates the corrosion reaction), while the cathode will be protected, resulting in the protruding part being corroded first, the oxide film in the protruding part is corroded and dissolved, and the surface will become a metal element, making it easier to deposit precious metal particles. On the other hand, the protruding part usually has a higher surface energy due to its shape characteristics, and high surface energy means that the surface atoms or molecules have higher activity and are more likely to react with other substances. Therefore, in an acidic environment, the protruding part is more likely to dissolve due to its higher surface energy. In addition, the convex part often has stress concentration in structure, which will cause the material to change in the microstructure of the area, such as lattice distortion, increased dislocation, etc., which makes the convex part with stress concentration more likely to dissolve in an acidic environment, and the surface of the corresponding convex position will become a metal element, making it easier to deposit precious metal particles. The surface of the metal part treated by this embodiment has a low precious metal load while having high electrical conductivity, corrosion resistance and durability, ensuring its long life under working conditions.

[0087] Embodiment 6

[0088] like Figure 6 As shown, it is a flow chart of a fifth embodiment of a method for preparing a metal component suitable for producing hydrogen by electrolysis of water in the present application. In this embodiment, the preparation method includes:

[0089] S1. Constructing micron-sized metal particles with a particle size of 0.5 μm to 25 μm on the surface of the sample by arc spraying;

[0090] S2. Use oxalic acid with a concentration of 5% to 20% to pickle the sample at a temperature of 25 to 90°C for 5 minutes to 2 hours;

[0091] S3. After pickling, rinse the sample repeatedly with deionized water, wipe it dry and set aside;

[0092] S4. Perform physical vapor deposition on the pickled sample and control the size and distribution of the precious metal particles by adjusting the power, target spacing and deposition time.

[0093] Specifically, in this embodiment, in step S1, micron-sized metal particles with a particle size of 10 μm are constructed on the sample surface by arc spraying, preferably micron-sized arc-shaped metal particles. It should be noted that constructing micron-sized arc-shaped metal particles corresponding to the pre-deposition position on the sample surface is only a preferred method of this application. Specifically, micron-sized metal particles of other shapes corresponding to the pre-deposition position can also be constructed on the sample surface, as long as a protrusion can be formed relative to the sample surface. In step S2, hydrochloric acid with a concentration of 12% is used for pickling, and heat treatment is performed during pickling. The heating temperature is 85°C and the pickling time is 35 minutes. The pickling method can be static pickling, ultrasonic pickling, stirring pickling, electrochemical pickling, etc., and the oxide film on the surface of the bipolar plate and the porous transport layer is removed by adjusting the above pickling condition parameters (the porous transport layer is a porous structure, and the parameters and methods are adjusted to make the surface exposed area fully pickled, so as to facilitate the attachment of precious metal particles in the exposed area). In step S3, the titanium substrate sample after pickling is washed with deionized water for more than 3 times. In step S4, physical vapor deposition is performed on the pickled sample, and the size and distribution of the precious metal particles are controlled by adjusting the power, target spacing and deposition time. Specifically, the platinum target and the sample are connected to the negative pole of a DC power supply or grounded, and the DC power supply provides the electric field required for sputtering. Specifically, this embodiment summarizes the power of magnetron sputtering DC sputtering is 500W, the target spacing is 8cm, the sputtering time is 20min, and the precious metal loading of the formed precious metal coating is 0.3mg / cm on both sides. 2 Below, the average single-side coating thickness is below 70nm, and the size of the formed precious metal particles is between 10nm and 40nm.

[0094] In this embodiment, the power, target spacing and deposition time are adjusted by physical vapor deposition to control the size and distribution of the precious metal particles, so that the precious metal loading of the precious metal coating on the surface of the final sample is 0.3 mg / cm on both sides. 2 In addition, since the non-precious metal doped coating is easy to passivate under working conditions, it has good corrosion resistance, but the contact resistance increases due to the formation of the passivation film, and the durability is poor; and this embodiment deposits a layer of precious metal on the micron-sized metal particles composed of several corrosion-resistant elements such as Ti, Zr, Nb, Ta, Mo and W, but does not ensure that the precious metal loading is 0.3 mg / cm on both sides. 2 The surface of the metal component after the treatment of this embodiment has a low precious metal load while having high conductivity, corrosion resistance and durability, ensuring its long life under working conditions.

[0095] The above describes specific embodiments of the present invention. Other embodiments are within the scope of the appended claims. In some cases, the actions or steps recorded in the claims can be performed in an order different from that in the embodiments and still achieve the desired results. In addition, the processes depicted in the accompanying drawings do not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.

[0096] In the description of the embodiments of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiments of the present invention. In the embodiments of the present invention, the schematic representations of the above terms do not necessarily refer to the same embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in the embodiments of the present invention and the features of the different embodiments or examples, without contradiction.

[0097] In addition, the terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features, and do not include any ordering. Thus, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features and are used to distinguish each other. In the description of the embodiments of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0098] Any process or method description in a flowchart or otherwise described herein may be understood to represent a module, fragment or portion of code comprising one or more executable instructions for implementing the steps of a custom logical function or process, and the scope of the preferred implementation of the embodiments of the present invention includes alternative implementations in which functions may not be performed in the order shown or discussed, including performing functions in a substantially simultaneous manner or in reverse order depending on the functions involved, which should be understood by technicians in the technical field to which the embodiments of the present invention belong.

[0099] The above description is only a preferred embodiment of the embodiment of the present invention and is not intended to limit the embodiment of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiment of the present invention should be included in the scope of protection of the embodiment of the present invention.

Claims

1. A metal component suitable for producing hydrogen by electrolysis of water, characterized in that: The metal component has a precious metal coating, and the precious metal loading of the precious metal coating is 0.3 mg / cm on both sides. 2 The average single-sided coating thickness is below 70 nm; the precious metal particles on the precious metal coating are uniformly distributed and the particle size of the precious metal particles is between 10 nm and 180 nm, wherein the difference between the maximum particle size and the minimum particle size of the precious metal particles is less than 130 nm, and the average spacing between the precious metal particles is 38 to 227 nm, and the average spacing is defined as the average value of the distances to the N precious metal particles closest to all the precious metal particles, 10 ≥ N ≥ 2.

2. The metal component according to claim 1, characterized in that The metal component is a titanium bipolar plate or a porous transmission layer.

3. A method for preparing a metal component suitable for electrolyzing water to produce hydrogen, for preparing a precious metal coating on a metal component as claimed in claim 1 or 2, characterized in that: The following steps are involved: The size of the precious metal particles and the distribution on the sample surface during the subsequent deposition process are preliminarily controlled by adjusting the condition parameters of the pickling process; the condition parameters include a pickling temperature range of 25 to 90° C. and a pickling time of 5 min to 2 h; The size of the precious metal particles and their distribution on the sample surface are ultimately controlled by electrodeposition or physical vapor deposition, thereby ultimately producing a metal component with a precious metal coating; Among them, the control parameters of electrodeposition need to meet the current density of 1mA ~ 200mA / cm 2 , the duty cycle is 0% to 60%, and the deposition time is 5s to 600s; the control parameters of physical vapor deposition must meet the etching power of 50 to 300W, the etching time of 5 to 60min, the sputtering power of 50 to 500W, the heating temperature of 100 to 1000°C, and the deposition time of 30 to 3600s.

4. The preparation method according to claim 3, characterized in that: The steps of preliminarily controlling the size of the precious metal particles and the distribution on the sample surface during the subsequent deposition process by adjusting the condition parameters of the pickling process include: applying a negative potential to the sample by electrochemical pickling to cause hydrogen evolution and hydrogen permeation on its surface, the surface hydrogen evolution can make the surface energy of the exposed part of the sample tend to be consistent, and the probability of depositing precious metal particles tend to be consistent; the surface hydrogen permeation can reduce the precious metal ions on the surface of the sample due to the release of hydrogen in the sample during the deposition process, thereby realizing the deposition of precious metal particles with small particle size.

5. The preparation method according to claim 3, characterized in that: The condition parameters also include the pickling solution being selected from one or a combination of oxalic acid, hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid.

6. The preparation method according to claim 3, characterized in that: Before the step of preliminarily controlling the size of the precious metal particles and the distribution on the sample surface in the subsequent deposition process by adjusting the condition parameters of the pickling process, the method includes: presetting the pre-deposition position of the precious metal particles on the sample surface by physical means.

7. The preparation method according to claim 6, characterized in that: The step of presetting the pre-deposition position of the precious metal particles on the sample surface by physical means includes: preparing sub-microholes corresponding to the pre-deposition position on an acid-base resistant and high-temperature resistant tape above 100°C or a high-temperature resistant mask plate, and pasting it on the sample surface.

8. The preparation method according to claim 7, characterized in that: The step of preparing sub-microholes corresponding to the pre-deposition position on an acid- and alkali-resistant tape or a high-temperature-resistant mask plate includes: using ultrafast laser drilling technology to drill holes with a diameter between 100nm and 10μm on an acid- and alkali-resistant tape or a high-temperature-resistant mask plate made of PET, PTFE, PVC or PI to form a design pattern corresponding to the pre-deposition position.

9. The preparation method according to claim 6, characterized in that: The step of presetting the pre-deposition position of the noble metal particles on the sample surface by physical means comprises: constructing micron-sized arc-shaped metal particles corresponding to the pre-deposition position on the sample surface.

10. The preparation method according to claim 9, characterized in that: The step of constructing micron-sized arc-shaped metal particles corresponding to the pre-deposition position on the sample surface includes: constructing micron-sized metal particles with a particle size of 0.5μm to 25μm on the sample surface by flame spraying, arc spraying, plasma spraying or thermal spraying to form a design pattern corresponding to the pre-deposition position.

11. The preparation method according to claim 10, characterized in that: The micron-sized arc-shaped metal particles can withstand harsh working conditions of water electrolysis to produce hydrogen and maintain corrosion resistance, and the metal component is selected from one or more corrosion-resistant elements of Ti, Zr, Nb, Ta, Mo and W.

12. The preparation method according to claim 11, characterized in that: The steps of ultimately controlling the size and distribution of the precious metal particles on the sample surface by electrodeposition or physical vapor deposition include: controlling the size and distribution of the precious metal particles by adjusting the parameters of the pulse power supply, current, frequency, duty cycle and deposition time by electrodeposition; or controlling the size and distribution of the precious metal particles by adjusting the power, target spacing and deposition time by physical vapor deposition.

Citation Information

Patent Citations

  • Preparation method of noble metal super-amphiphobic surface

    CN108525970A

  • Anode gas diffusion layer and preparation method and application thereof

    CN115216798A

  • Non-close-packed noble metal nanoparticle ordered dot matrix and preparation method thereof

    CN116031326A

  • High-conductivity corrosion-resistant porous titanium diffusion layer and preparation method and application thereof

    CN117947370A

  • Metal fine particle carrier and its manufacturing method

    JP2009178644A